Polityka decentralizacji administracji we Francji w latach 1950-1983 - Pelissionnier, Gérard; Perreur, Jacky (Wydział Prawa i Administracji UAM, 1984)
A study of the process of administrative decentralization in the period of 1950 - 1983 is the subject of the present article. The substantial part of the discussion is devoted to presentation of actions undertaken after 1981, i.e. in the course of changes brought about by presidential and parliamentary elections. As far as the period to 1931 is concerned, the authors view its organizational moves as a manifestation of deconcentration of power tendencies, rather that a genuine decentralization. Legal acts enacted after 1981 prove a real will of the legislator to carry out a decentralization process. The article discusses in detail all acts and decrees regulating a new competence division between local communities and the state, changes in executive powers in regions and departments, new functions of regions,, new role of state representatives in communities, principles of financing and control a posteriori, possibilities of communities intervention in economic and social matters. All that results in eliminating the state's tutelage on local communities in the respect of administration and financing. The period which has passed since 1981 is too short to allow drawing any far reaching conclusions. It is therefore advised to undertake an attempt at resuming that new stage of decentralization after a certain time.
Policies of administrative decentralization in France in the years of 1950-1983